2008
DOI: 10.1016/j.nuclcard.2007.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Arterial wall uptake of fluorodeoxyglucose on PET imaging in stable cancer disease patients indicates higher risk for cardiovascular events

Abstract: Extensive arterial 18FDG uptake might be an indicator of an evolving atherosclerotic process and should be mentioned in PET/computed tomography reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(92 citation statements)
references
References 36 publications
3
82
1
4
Order By: Relevance
“…In this study, we observed a modest inverse relationship between BAT activity and arterial inflammation. Given that PET/CT measures of arterial inflammation have repeatedly been shown to predict CVD events (13,15,24), we hypothesized that BAT activation would also be associated with CVD events. Indeed, we observed that in individuals who experienced CVD events, arterial 18 F-FDG uptake was higher whereas BAT uptake was significantly lower.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed a modest inverse relationship between BAT activity and arterial inflammation. Given that PET/CT measures of arterial inflammation have repeatedly been shown to predict CVD events (13,15,24), we hypothesized that BAT activation would also be associated with CVD events. Indeed, we observed that in individuals who experienced CVD events, arterial 18 F-FDG uptake was higher whereas BAT uptake was significantly lower.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies reported significant correlations between focally increased 18 F-FDG uptake in the walls of large arteries and the presence of conventional cardiovascular risk factors (22)(23)(24)(25)(26), as if risk factors predispose to inflammatory changes resulting in formation of plaques at risk for rupture. In all these studies, increased vascular wall 18 F-FDG uptake was most strongly correlated with patient age.…”
Section: Correlation Of Baseline Parametersmentioning
confidence: 97%
“…To our knowledge, only a single study to date has systematically investigated the covariance of increased 18 F-FDG uptake and calcifications of the arterial wall with the occurrence of vascular events (24). In that study, on a series of 101 stable cancer patients, most of the registered vascular events occurred before the PET/CT scan.…”
Section: Outcome Events and Survival Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 In addition, higher arterial FDG uptake is associated with a substantially increased risk for subsequent stroke and MI. [33][34][35] Taken together, these studies provide justification for using arterial FDG-PET/CT imaging to provide a meaningful measure of arterial inflammation in human clinical studies.…”
Section: See Related Article Pp 372-380mentioning
confidence: 85%